A seção o português é uma figura, de Marcílio Godói, em diálogo com gêneros discursivos nas esferas jornalística, científica e pedagógica - Borges, Marilurdes Cruz [UNESP] (2015)
The present research aims at investigating and analysing the sense and the saying project of the author-creator of the section Portuguese is a figure, monthly published in Língua Portuguesa magazine. It also aims at verifying how the enunciate, established in the section, dialogues with different activities and discursive genres and how it answers the didactical-pedagogical practices in the teaching of Portuguese and Literature. The observation of the responsive acts and dialogical relations which are shown in the section, let us comprehend how the educational practices are reflected and re-signified by Marcílio Godoi's enunciate, in the Língua Portuguesa magazine. Questions on author and hero, dialogue, responsive act, activity field, concrete enunciate and discursive genre, presented by Mikhail Bakhtin and his followers of the Bakhtin Circle, are the theoretical foundations of the investigation. The corpus of analysis is built by some sections published on Portuguese is a figure, from May, 2008 to December, 2014, although the research, in order to know the editing project of the magazine, has contemplated all the publications of the magazine, from n.1 to n.110. The developed investigation aims to be analytical-interpretative, in which the corpus is expanded by literary and critical texts and the dialogical relations are observed in different viewpoints: through the enunciates which are in the section - caricature, citation and biographical profile -; through the section and the enunciative proposal of the magazine; through the section and the journalistic, scientific and educational fields; through the section and some discursive genres that are typical of each communication field. In the analysis and interpretation, some hypothesis which came up in terms of the sense and the saying project of the author-creator of the section Portuguese is a figure, are confirmed, taking into account that, in the dialogues undertaken with the ...